Development of Student Worksheets Integrating Local Wisdom on Work and Simple Machines in South Papua - Helena Kudmasa; Algiranto Algiranto; Jeffri Parrangan (CV. Dharma Samakta Edukhatulistiwa, 2026)
This study aims to develop local wisdom–based student worksheets on the topic of work and simple machines for junior high school students in South Papua. The limited availability of contextual teaching materials that integrate local cultural practices has restricted students’ ability to connect physics concepts with real-life experiences. This study employed a Research and Development (R&D) approach using a modified 4D model limited to the development stage. The participants consisted of material experts, media experts, a science teacher, and ten students in a limited trial. Data were collected using validation sheets and practicality questionnaires and analyzed descriptively using percentage criteria. The results indicate that the developed worksheets were categorized as very feasible by material experts (83%) and feasible by media experts (68%). In addition, the worksheets were considered very practical based on teacher responses (89%) and student responses (90%). These findings suggest that integrating South Papuan local wisdom into instructional materials can enhance contextual understanding and student engagement in physics learning. The novelty of this study lies in embedding local cultural practices into learning materials on work and simple machines. Therefore, the developed worksheets are feasible and practical for supporting meaningful science learning.